The Lingering Shadow: Long-Term Effects on COVID-19 Survivors (Nepal Journal of Epidemiology, 2025)
The editorial message is unequivocal: Long COVID cannot be sidelined. Governments must enhance access to multidisciplinary care clinics, fund long-term research, and embed mental health services within recovery programs. Vaccination reduces risk by 10-12%, reinforcing that prevention remains essential. For survivors, recognition is critical acknowledging their struggles and investing in their futures. As research shows, organ damage may be persistent, with long-term effects still emerging. Ignoring this shadow will only deepen the pandemic’s legacy; confronting it directly could reshape resilience in the post-COVID world.